Transformation-dependent alterations in the oligosaccharides of Prague C Rous sarcoma virus glycoproteins. - Hunt, L A (1981)
The influence of cell transformation on the glycosylation of viral envelope glycoproteins was examined by high-resolution gel filtration and specific glycosidase digestions of 3H-sugar-labeled glycopeptides from nondefective and transformation-defective Prague C strains of Rous sarcoma virus replicated in fibroblasts from the same chicken embryo. The major difference in glycosylation attributable to the viral transformation of the host cells was an increase in this relative amount of larger acidic-type oligosaccharides containing additional "branch" sugars (NeuNAc-Gal-GlcNAc-) compared with the smaller acidic-type and neutral-type oligosaccharides. There was also a shift in size distribution of neutral-type oligosaccharides toward smaller oligomannosyl cores in the transforming versus nontransforming virus glycopeptides. These alterations were consistent with a transformation-dependent increase in the extent of intracellular processing of a common precursor structure for the asparagine-linked oligosaccharides of Rous sarcoma virus.